Pain : brain stimulation in the treatment of pain - Knotkova, Helena; Cruciani, Ricardo; Merrick, Joav, 1950- (Disability Studies., 2010)
Recent research suggests that chronic pain affects as many as three percent of the worldwide population and there is evidence that chronic pain patients are twice as likely to commit suicide compared with the healthy population. It should also be remembered that the lifetime prevalence of suicide attempts in the chronic pain population is about ten percent. Although various innovative pharmacological preparations and formulas have been implemented into clinical practice in recent years, chronic pain in many patients has not been successfully maintained at an acceptable level, thus not allowing the patients to resume their life activities. Despite remarkable advances in pain management, chronic pain remains undertreated, depicting the need for new therapeutic approaches to chronic pain.